تعليم الخط العربي في المراحل المختلفة على ضوء نظرية الفضيلة عند - Muhammad Nur (Universitas Negeri Malang, 2022)
The teaching of calligraphy to pupils at various educational levels requires a continuous process supported by teachers who master the field, as well as the preparation of supporting facilities. However, this process only touched on the material aspect, although pupils have a spiritual aspect that also needs attention. This research attempts to present a plausible view of the Miskawaih's theory of virtue through the virtue of wisdom, chastity, courage and justice and to propose it to complete the teaching of calligraphy until it reaches its goal.